Nummular eczema in childhood: a retrospective study of 515 cases. - Patrizi, A; Ricci, G; Neri, I; Marzaduri, S; Bellini, F; Giacomini, F; Masi, M (European Journal of Pediatric Dermatology, 2006)
The aim of this study was to evaluate the frequency of the association between nummular eczema and atopic dermatitis (AD) in children, given that in adults nummular eczema is associated with AD in about 10% of cases. 5,700 children affected by eczema were referred to the Pediatric Unit of our Dermatology Department between 1992 and 2002. Of these, 515 (9%) presented nummular eczema. The patients consisted of 333 males (64.7%) and 182 females (35.3%). The patches of eczema were multiple in 477 (92.6%) cases, while the remaining 38 (7.4%) had only one lesion. The onset of clinical manifestations ranged between 40 days of life and 12 years; 420 (81.6%) patients were under 2 years. Allergologic tests and a follow-up of at least 6 months were available in 376 patients: 261 (69.4%) were affected by AD, 14 (3.7%) had contact dermatitis and in 101 (26.9%) cases a definitive cause could not be established. Our data show that the association between nummular eczema and AD is higher in children than in adults.